CUSTOMER SATISFACTION WITH ONLINE BANKING - Okojie, Stella efe (2005)
Measuring user satisfaction with information systems has attracted widespread research attention, given it is often used as an indicator of success. The internet has allowed applications to be extended to customers of an organization, where interaction can take place through a web site, typically from home or office. With the increasing amount of research into internet marketing and electronic commerce (e-commerce), service quality in online environments has become recognised as an important factor in determining the success or failure of electronic commerce.